2014
DOI: 10.1051/0004-6361/201322572
|View full text |Cite
|
Sign up to set email alerts
|

Long-period intensity pulsations in the solar corona during activity cycle 23

Abstract: We report on the detection (10 σ) of 917 events of long-period (3 to 16 hours) intensity pulsations in the 19.5 nm passband of the SOHO Extreme ultraviolet Imaging Telescope. The data set spans from January 1997 to July 2010, i.e the entire solar cycle 23 and the beginning of cycle 24. The events can last for up to six days and have relative amplitudes up to 100%. About half of the events (54%) are found to happen in active regions, and 50% of these have been visually associated with coronal loops. The remaini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
97
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(107 citation statements)
references
References 54 publications
10
97
0
Order By: Relevance
“…In addition, recovery of four-hour and nine-hour periods in the o1 box (in Figure 3) and the qs1 box (in Figure 5b) lie at the edges of the typical range of periods reported in Telloni et al (2013), but all are well within the range of periods previously recovered for a range of solar coronal structures (e.g. Ivanov, 1983;Foullon, Verwichte, and Nakariakov, 2004;Smirnova et al, 2013;Auchère et al, 2014). Furthermore, the o1 and qs1 detections are both marginally above global confidence levels and rely on the form of the fitted background power derived from Equation 1.…”
Section: Recovery Of Periodic Signaturessupporting
confidence: 74%
See 1 more Smart Citation
“…In addition, recovery of four-hour and nine-hour periods in the o1 box (in Figure 3) and the qs1 box (in Figure 5b) lie at the edges of the typical range of periods reported in Telloni et al (2013), but all are well within the range of periods previously recovered for a range of solar coronal structures (e.g. Ivanov, 1983;Foullon, Verwichte, and Nakariakov, 2004;Smirnova et al, 2013;Auchère et al, 2014). Furthermore, the o1 and qs1 detections are both marginally above global confidence levels and rely on the form of the fitted background power derived from Equation 1.…”
Section: Recovery Of Periodic Signaturessupporting
confidence: 74%
“…Periods of the order of an hour or longer have been recovered for several decades across a range of coronal instruments (e.g. by Ivanov, 1983;Foullon, Verwichte, and Nakariakov, 2004;Popescu et al, 2005;Auchère et al, 2014). The Solar Dynamics Observatory (SDO: Pesnell, Thompson, and Chamberlin, 2012) allows for continuous high-resolution and high-cadence measurements across a suite of instruments; this observatory has also contributed significantly to studies of long-period oscillatory features in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…There are also indicators that hydrodynamic evolution along coronal loops can be quite common, especially for active regions. These include observations of coronal rain and catastrophic cooling cycles (Schrijver 2001;Antolin & Rouppe van der Voort 2012;Antolin et al 2015), as well as pervasive cooling signatures observed in extreme ultraviolet (Viall & Klimchuk 2011Auchère et al 2014;Froment et al 2015) and soft X-Ray imaging (Ugarte- Urra et al 2006). A successful heating model should be plausibly consistent with such observations.…”
Section: Introductionmentioning
confidence: 92%
“…Processing more than 13 years of quasi-continuous 12 minute-cadence observations with the 19.5nm passband of the Solar and Heliospheric Observatory (Domingo et al 1995) Extreme-ultraviolet Imaging Telescope (Delaboudinière et al 1995), we discovered 499 periodic (3-16 hr) intensity pulsation events in on-disk active regions, 268 of which are clearly associated with loops, and some lasting for up to six days (Auchère et al 2014). Froment (2016) found more than 2000 similar events in six years of images taken in the six coronal passbands of the Solar Dynamics Observatory (SDO; Pesnell et al 2012) Atmospheric Imaging Assembly (AIA; Lemen et al 2012).…”
Section: Contextmentioning
confidence: 99%